2006
DOI: 10.1590/s1679-62252006000400007
|View full text |Cite
|
Sign up to set email alerts
|

Ion fluxes in silver catfish (Rhamdia quelen) juveniles exposed to different dissolved oxygen levels

Abstract: Low dissolved oxygen levels in the water (hypoxia) can be provoked by oxygen consumption by fish and other organisms, organic matter decomposition, phytoplankton blooms, and temperature increase. The objective of the present study was to investigate Na + , Cl -, K + , and ammonia fluxes in silver catfish (Rhamdia quelen) exposed to different dissolved oxygen levels. Juveniles (9 ± 1g) maintained at 6.0 mg.L -1 dissolved oxygen were transferred to four 40 L aquaria with different dissolved oxygen levels (in mg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
11
2
Order By: Relevance
“…Low DO levels (3.5mg L -1 ) for 6-24h increased plasma Na + , K + and Cl -levels in the silver catfish irrespective to NH 3 levels in the water (Table 2). In disagreement with the present results, ROSSO et al (2006) demonstrated that exposure to 2.5-3.5mg L -1 DO levels for 1h increased Na + and Cl -loss in silver catfish. However, these ion losses in hypoxia observed by ROSSO et al (2006) were similar to control values 24h later, but intermediate measurements were not performed.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Low DO levels (3.5mg L -1 ) for 6-24h increased plasma Na + , K + and Cl -levels in the silver catfish irrespective to NH 3 levels in the water (Table 2). In disagreement with the present results, ROSSO et al (2006) demonstrated that exposure to 2.5-3.5mg L -1 DO levels for 1h increased Na + and Cl -loss in silver catfish. However, these ion losses in hypoxia observed by ROSSO et al (2006) were similar to control values 24h later, but intermediate measurements were not performed.…”
Section: Resultscontrasting
confidence: 99%
“…In disagreement with the present results, ROSSO et al (2006) demonstrated that exposure to 2.5-3.5mg L -1 DO levels for 1h increased Na + and Cl -loss in silver catfish. However, these ion losses in hypoxia observed by ROSSO et al (2006) were similar to control values 24h later, but intermediate measurements were not performed. Consequently, a recovery of ion losses in Ciência Rural, v.39, n.6, set, 2009. this species could appear between 1h and 24h, thus justifying the results of the present study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Fish were weighed at the end of the flux experiment. Previous experiments of Rosso et al (2006) demonstrated that net ion fluxes of juveniles maintained for 24 hours in chambers were not significantly different from the fluxes of those which measurements started around 10 min. after placing them in the chambers.…”
Section: Net Ion Fluxesmentioning
confidence: 82%
“…Stress increases gill blood flow and paracellular permeability, resulting in ion loss (Cech et al, 1996). Recovery is variable depending on the intensity of stress and species (Gonzalez & McDonald, 1994;Baldisserotto & Val, 2002;Rosso et al, 2006). In the present experiment apparently stress was reduced after 2 h, since net Ca 2+ fluxes in tamoatás in black water and well water became net influxes, and values were similar to those determined by Wilson et al (1999) for the same species and Brycon erythropterum (= Brycon cephalus) exposed to well water at pH 6.0.…”
Section: Discussionmentioning
confidence: 99%